Adapting to a Changing Colorado River Making Future Water Deliveries More Reliable Through Robust Management Strategies - Groves, David G. (RAND Corporation, 2013)
The 2012 Colorado River Basin Study evaluated the resiliency of the Colorado River system over the next 50 years to climate change and other factors, and then compared different options and strategies for ensuring successful management of the river's resources. This report describes RAND's contribution to this study. It focuses on the Robust Decision Making methodologies used to identify vulnerabilities and compare portfolios of options.